2007
DOI: 10.1111/j.1365-2583.2007.00763.x
|View full text |Cite
|
Sign up to set email alerts
|

Expressed sequence tags from the midgut of Epiphyas postvittana (Walker) (Lepidoptera: Tortricidae)

Abstract: The midgut is a key tissue in insect science. Physiological roles include digestion and peritrophic membrane function, as well as being an important target for insecticides. We used an expressed sequence tag (EST) approach to identify candidate genes and gene families involved in these processes in the light brown apple moth, Epiphyas postvittana (Walker) (Lepidoptera: Tortricidae). Two cDNA libraries were constructed from dissected midgut of third to fifth instar larvae. Clustering analysis of 6416 expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 89 publications
2
42
0
1
Order By: Relevance
“…The target site for Bt toxins is believed to be the midgut, a dynamic tissue which plays a vital role in metabolism, digestion, and detoxification. In Lepidoptera, previous studies have focused on the role of proteases, lipases and carbohydrases in digestion, and carboxylesterases, glutathione-s-transferases and cytochrome P450s in xenobiotic metabolism in the midgut 13, 14, 15. With the advent of genomics and its “omics” tools, current research looked more closely at the physiological and toxicological changes at a global level instead of focusing on individual genes in the midgut.…”
Section: Introductionmentioning
confidence: 99%
“…The target site for Bt toxins is believed to be the midgut, a dynamic tissue which plays a vital role in metabolism, digestion, and detoxification. In Lepidoptera, previous studies have focused on the role of proteases, lipases and carbohydrases in digestion, and carboxylesterases, glutathione-s-transferases and cytochrome P450s in xenobiotic metabolism in the midgut 13, 14, 15. With the advent of genomics and its “omics” tools, current research looked more closely at the physiological and toxicological changes at a global level instead of focusing on individual genes in the midgut.…”
Section: Introductionmentioning
confidence: 99%
“…EST analysis of midguts has been reported in several insects, such as Bombyx mori [1], Drosophila melanogaster [2], Manduca sexta [3], Chironomus tentans [4], Mamestra configurata [5], Spodoptera frugiperda [6], Epiphyas postvittana [7], Choristoneura fumiferana [8], Anopheles stephensi [9] and Plutella xylostella [10]. However, it is found that there are always certain percentages (ranged from 13% to 30%) of ESTs that show low similarities or no similarity to sequences deposited in the public databases.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria present in the Drosophila gut are thought to release peptidoglycan fragments that bind to specific PGRP (peptidoglycan recognition protein) receptors and induce the imd pathway (13-15). Simpson et al (16) described a sequence (EpGRP1) with similarity to ␤1,3-glucanbinding proteins from Anopheles gambiae and Bombyx mori in ESTs derived from the larval midgut of Epiphyas postvittana. In a proteomic study of the lumen contents of larval midgut of Helicoverpa armigera, we (17) discovered a similar protein that we named GH16betaGRP-1 (glycosyl hydrolase family 16, ␤-glucan recognition protein 1) secreted into the lumen.…”
mentioning
confidence: 99%